Клещи краснотелки рода Leptotrombidium (Acariformes, Trombiculidae) из Ирана - Кудряшова, Н.И. (Вестник зоологии, 1976)
7 species of chiggers from the Leptotrombidium genus are found on rodents from Iran. A description and drawings are given for the following 5 species: L. (Leptotrombidium) subsilvaticum sp. n., L. (E.) limpidum sp. n., L. (E.) biconcavurn sp. n., L. (E.) kazeruni sp. n. Data are also presented on the finding places in Iran and distribution of L. (L.) silvaticum H u s h c h a et Schluger, 1967 and L. (E.) jayewickremei (Womersley, 1952).